Manajemen Marketing Pendidikan di Pondok Pesantren Al-Istiqomah Tanjungsari Petanahan Kebumen - Setiawan, Abdi; Sholeh, Agus Nur (IAINU Kebumen, 2025)
This study uses a qualitative approach with a type of field research (field research). The research subjects were Islamic boarding school caretakers, the chairman of the Foundation, media team and students. Data collection techniques using observation, interviews and documentation. In this case, the sources were the caretakers of the Islamic Boarding School, the chairman of the Foundation, the media team and students at the Al-Istiqomah Islamic Boarding School, Tanjungsari Petanahan, Kebumen. The data analysis technique uses qualitative analysis data such as data reduction, data presentation and drawing conclusions. The results of the study show that the education marketing management of the media team at the Al-Istiqomah Tanjungsari Petanahan Kebumen Islamic boarding school determines planning, organizing, implementing and supervising in order to achieve effective and efficient goals. The results of the media team's education marketing management at the Al-Istiqomah Islamic Boarding School Tanjungsari Petanahan Kebumen are the increasing number of students every year and being increasingly recognized by the whole community, both from the local community, people outside Kebumen and even abroad